1964
DOI: 10.1002/ar.1091500306
|View full text |Cite
|
Sign up to set email alerts
|

The extent of cardiac muscle in the great veins of the dog

Abstract: The extent and arrangement of cardiac muscle in the great veins of adult dogs of both sexes was investigated. Cardiac muscle was found for varying distances in the venae cavae and pulmonary and azygos veins in all animals. The average distances which the muscle extended into these vessels in the beagles were: 1.88, 0.859, 0.525, and 0.622cm. Similar measurements in the poodle were: 1.35, 0.705, 0.764, and 0.690 cm and in the shepherd: 3.05, 1.36, 1.22, and 0.926 cm. Both the venae cavae and pulmonary veins co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
2

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 9 publications
1
12
0
2
Order By: Relevance
“…Similar discussions have concerned the pulmonary veins (AMANO, 1933;TAKING and EZAKI, 1934;OTTERBACH, 1938;BURGH and ROMNEY, 1954;KLAVINS, 1963;CARROW and CALHOUN, 1964;ALMEIDA et al, 1975), since the cardiac muscle is well developed in their walls. Although node-like cells were reported in rat pulmonary veins (MASANI, 1986), we could not find specialized muscle fibers in either the superior or inferior venae cavae.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Similar discussions have concerned the pulmonary veins (AMANO, 1933;TAKING and EZAKI, 1934;OTTERBACH, 1938;BURGH and ROMNEY, 1954;KLAVINS, 1963;CARROW and CALHOUN, 1964;ALMEIDA et al, 1975), since the cardiac muscle is well developed in their walls. Although node-like cells were reported in rat pulmonary veins (MASANI, 1986), we could not find specialized muscle fibers in either the superior or inferior venae cavae.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have macroscopically and histologically demonstrated in several kinds of animals and human that the cardiac muscle is also present in the wall of the venae cavae adjacent to the heart (PAPEZ, 1920;HUSTEN, 1926;BENNINGHOFF, 1930;GLOMSET and GLOMSET, 1940;KARRER, 1959;THOMAS, 1959;CARROW and CALHOUN, 1964;NATHAN and ELIAKIM, 1966;NATHAN and GLOOBE, 1970;SPACH et al, 1972ENDO et al, 1994). The precise histological distribution and arrangement of the cardiac muscle in the venae cavae have been described for rats and dogs (CARROW and CALHOUN, 1964;ENDO et al, 1994). The rat superior vena cava contains well-developed circular or spiral muscle layers which are distributed from the right atrium to the root of the subclavian vein (ENDO et al, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Não foi detectada na paca a presença de musculatura cardíaca na veia cava conforme verificado na literatura para cães, suínos, ruminantes e Tupaia glis (Carrow & Calhoun 1964, Endo et al 1995. Características como presença de células cardíacas e células impulso condutoras também não foram observadas como mencionadas na literatura (Stieda 1877, Nathan & Eliakim 1966, Moubarak et al 2000, Ho et al 2001, Tagawa et al 2001, Mueller-Hoecker et al 2008.…”
Section: Discussão E Conclusõesunclassified
“…Na veia cava de cães, suínos e ruminantes foi observada presença de musculatura cardíaca (Carrow & Calhoun 1964), que também foi descrita para Tupaia glis (Endo et al 1995), uma espécie da ordem Scandentia, onde os autores atribuíram esta ocorrência como um fato comum em mamíferos considerados inferiores na escala zoológica.…”
Section: Introductionunclassified